Age-dependent effects of Igf2bp2 on gene regulation, function, and aging of hematopoietic stem cells in mice - Suo, Miaomiao (2022)
Increasing evidence links metabolism, protein synthesis, and growth signaling to impairments in the function of hematopoietic stem and progenitor cells (HSPCs) during aging. The Lin28b/Hmga2 pathway controls tissue development, and the postnatal downregulation of this pathway limits the self-renewal of adult vs fetal hematopoietic stem cells (HSCs). Igf2bp2 is an RNA binding protein downstream of Lin28b/Hmga2, which regulates messenger RNA stability and translation. The role of Igf2bp2 in HSC aging is unknown. In this study, an analysis of wild-type and Igf2bp2 knockout mice showed that Igf2bp2 regulates oxidative metabolism in HSPCs and the expression of metabolism, protein synthesis, and stemness-related genes in HSCs of young mice. Interestingly, Igf2bp2 expression and function strongly declined in aging HSCs. In young mice, Igf2bp2 deletion mimicked aging-related changes in HSCs, including changes in Igf2bp2 target gene expression and impairment of colony formation and repopulation capacity. In aged mice, Igf2bp2 gene status had no effect on these parameters in HSCs. Unexpectedly, Igf2bp2-deficient mice exhibited an amelioration of the aging-associated increase in HSCs and myeloid-skewed differentiation. The results suggest that Igf2bp2 controls mitochondrial metabolism, protein synthesis, growth, and stemness of young HSCs, which is necessary for full HSC function during young adult age. However, Igf2bp2 gene function is lost during aging, and it appears to contribute to HSC aging in 2 ways: the aging-related loss of Igf2bp2 gene function impairs the growth and repopulation capacity of aging HSCs, and the activity of Igf2bp2 at a young age contributes to aging-associated HSC expansion and myeloid skewing.